Dynamic Inter-Slice Resource Allocation Algorithm for RAN Slicing Support in UAV - Cho, Jun Woo; Lee, Choong Hee; Park, Hyung Won; Kim, Jae Hyun (Journal of Korean Institute of Communications and Information Sciences, 2021)
Unmanned aerial vehicles (UAVs) can apply radio access network (RAN) slicing to satisfy the quality of services (QoS) of various services in the 5G ecosystem. However, it is necessary to efficiently distribute limited radio resources to each slice since UAV has limited functions that can be mounted. Besides, it should be considered in resource allocation that 5G system support various type of physical resource block (PRB) because of QoS In this paper we propose a dynamic inter-slice resource allocation algorithm that maximizes the resource efficiency by considering service QoS. It periodically considers service distribution in a dynamic network environment, and then selects the best PRB in consideration of QoS and resource efficiency and performs resource allocation.
Keywords: communication; Communication Sciences; Network; Neutral systems; signal processing